Effects of sex and estrous cycle on extended-access oxycodone self-administration and cue-induced drug seeking behavior - Patel, Bhumiben P.; Loweth, Jessica A. (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Increasing evidence indicates that sex is a factor that impacts the abuse liability and relapse vulnerability of prescription opioids like oxycodone. However, while women are more likely than men to be prescribed and to use these drugs, the impact of sex and ovarian hormones on prescription opioid use and relapse vulnerability remains unclear. Accurately assessing these measures is complicated by the fact that chronic opioid exposure can lower ovarian hormone levels and cause cycle irregularities. Methods: Adult male and female Sprague-Dawley rats self-administered oxycodone (0.1 mg/kg/infusion) under extended-access conditions (6 h/day, 10 days) followed by forced abstinence. Separate groups of animals received cue-induced seeking tests in a drug-free state during early (1-2 days) or later periods of abstinence (43-45 days). To track estrous cycle stage, animals were regularly vaginally swabbed throughout the study. Results: We observed oxycodone-induced estrous cycle dysregulation in the majority (~60%) of the animals during both self-administration and the first month of abstinence. In animals whose cycles were not dysregulated, we found a reduction in oxycodone intake during estrus compared to all other cycle stages (non-estrus). We also found that males but not females showed a time-dependent intensification or incubation of cue-induced oxycodone craving over the first 6 weeks of abstinence. This sex difference was estrous cycle-dependent, driven by a selective reduction in drug seeking during estrus. Discussion: These findings highlight the importance of tracking drug-induced estrous cyclicity and identify a clear impact of ovarian hormones on oxycodone taking and seeking behavior.